2003
DOI: 10.1901/jaba.2003.36-439
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Stereotypic Behavior: Examining the Effects of External Reinforcers

Abstract: Basic research has shown that behavioral persistence is often positively related to rate of reinforcement. This relation, expressed in the metaphor of behavioral momentum, has potentially important implications for clinical application. The current study examined one prediction of the momentum metaphor for automatically reinforced behavior. Participants were 3 children who had been diagnosed with an autism spectrum disorder and who engaged in stereotypic behavior maintained by automatic reinforcement. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
110
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 27 publications
7
110
0
Order By: Relevance
“…Nevin et al, 1990). This result has been replicated with a variety of reinforcers and species ranging from fish to humans (Mace et al, 1990;Cohen, 1996;Harper, 1999;Grimes and Shull, 2001;Ahearn et al, 2003;Igaki and Sakagami, 2004;Shahan and Burke, 2004). Nevin et al (1990) have suggested that such effects of the Pavlovian stimulus-reinforcer relation on the persistence of operant behavior are likely similar to other motivational effects attributed to arousal, a central motivational state, or the incentive-motivational properties of conditioned stimuli (e.g.…”
Section: Introductionmentioning
confidence: 83%
“…Nevin et al, 1990). This result has been replicated with a variety of reinforcers and species ranging from fish to humans (Mace et al, 1990;Cohen, 1996;Harper, 1999;Grimes and Shull, 2001;Ahearn et al, 2003;Igaki and Sakagami, 2004;Shahan and Burke, 2004). Nevin et al (1990) have suggested that such effects of the Pavlovian stimulus-reinforcer relation on the persistence of operant behavior are likely similar to other motivational effects attributed to arousal, a central motivational state, or the incentive-motivational properties of conditioned stimuli (e.g.…”
Section: Introductionmentioning
confidence: 83%
“…Another study found that children engaged in higher rates of repetitive behaviors while in the presence of an unfamiliar person as compared to a familiar person (Runco, Charlop, & Schreibman, 1986). Additionally, other research has provided evidence for the effect of tangible reinforcement on the frequency and duration of stereotypic behaviors (Ahearn, et al, 2003). These data collectively suggest that external stimuli, rather than only intrinsic automatic reinforcers, may also operate on stereotypy.…”
Section: Stereotypy As a Socially Mediated Behaviormentioning
confidence: 93%
“…However, another growing body of literature specifies that stereotypic behavior may be determined by other reinforcement contingencies (Kennedy, et al, 2000;Repp, et al, 1988). For example, stereotypy has been shown to operate under the control of social reinforcement (Durand & Carr, 1987) and tangible reinforcement contingencies (Ahearn et al, 2003). Interpretations of stereotypic behaviors should not presume that sharing a specific topography necessarily involves also belonging to the same response class.…”
Section: Stereotypy As An Operant Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, greater reinforcement rates produce greater resistance to disruption irrespective of whether the additional reinforcement is presented response independently, as in Podlesnik and Shahan (2009), dependent on the same response (e.g., Nevin, 1974;Nevin, Mandell, & Atak, 1983), or contingent upon a concurrently available response (e.g., Mauro & Mace, 1996;Nevin et al, 1990;Podlesnik, Bai, & Elliffe, 2012;Rau, Pickering, & McLean, 1996). These findings are generally robust and have been observed in a variety of animal species, ranging from fish to humans, as well as several response types and reinforcer manipulations (Ahearn, Clark, Gardenier, Chung, & Dube, 2003;Cohen, 1996;Grimes & Shull, 2001;Harper, 1999;Igaki & Sakagami, 2004;Mace et al, 1990;Shahan & Burke, 2004). However, exceptions to the finding that resistance to disruption is independent from baseline response rate responding have been observed (e.g., Lattal, 1989;Nevin, Grace, Holland, & McLean, 2001;Podlesnik, JimenezGomez, Ward, & Shahan, 2006).…”
mentioning
confidence: 77%